Government’s Efforts to Protect Pertamini’s Consumer Rights for Losses Obtained - Faradiba Najla Salsabila; Abraham Ferry Rosando (Universitas PGRI Madiun, 2023)
Disadvantages that are usually found by consumers are usually inappropriate dosages, inappropriate octane values, prices that are different from regulations issued by the Government to accidents such as an explosion at a Pertamini pump that threatens the lives of the pom owner or Pertamini consumers. This research is expected to be able to explain the Government's efforts to protect Pertamini consumers who experience losses. The method chosen for this research process is normative juridical, where this method is used to examine rules, doctrines and principles that are able to answer the problems of this research. The approach chosen to answer the problems of this research is the legal and conceptual approach. The primary source in reviewing this research is legislation that is closely related to consumer protection. Data collection techniques and processing of legal materials use library methods or library research. The results of this study Pertamini business owners must always be responsible for consumer losses. This is known as the Presumption of Always Responsible. Consumers can file a lawsuit for default if there is a previous agreement and it can be an illegal act if there is no mutual agreement but the consumer feels aggrieved. The fastest way to resolve this dispute is through the non-litigation route involving the BPSK compared to the litigation route using the Court. There are three general options in settlement through non-litigation steps, namely mediation, arbitration and conciliation